Use of Cannabis and Alcohol by patients diagnosed with trauma in a Health Emergency Unit (Research, Society and Development, 2022)
There are few data on the association of physical trauma and consumption of psychoactive substances. Objective: To investigate the use of marijuana and alcohol by trauma victims becomes important to subsidize prevention actions. Methods: 299 willingly given samples from individuals hospitalized in the years 2015-2017 due to trauma associated to the use of drugs of abuse were analyzed; the individuals were considered user of drugs of abuse either due to medical diagnosis or to self-reporting. Biological samples from the patients were first trialed for Cannabis; confirmation of cannabis use was performed via gas chromatography-mass spectrometry. Alcoholaemia was also investigated. Results: Males made up the majority of the assessed subjects (91.4%), their average age being 40 years. The major causes for trauma included traffic accidents (46.82%) followed by violence/aggression (26.77%). Toxicological trialing for cannabis resulted in 14.72% positive samples and alcoholaemia varied between 9.38 to 17.85%. Conclusion: The abusive use of Cannabis is a risk factor for accidents and violence leading to traumatic injuries. The age range between the second and fourth decade of life and the automotive steering were relevant predictors for the use of Cannabis. Epidemiological studies provide important information to support preventive measures, considering the scarcity of studies on this theme.